National surveillance of antimicrobial susceptibilities to dalbavancin, telavancin, tedizolid, eravacycline, omadacycline and other comparator antibiotics and serotype distribution of invasive Streptococcus pneumoniae isolates in adults: results from the Surveillance of Multicenter Antimicrobial Resistance in Taiwan (SMART) programme in 2017–2020. (September 2021) - Chien, Ying-Chun; Lee, Yu-Lin; Liu, Po-Yu; Lu, Min-Chi; Shao, Pei-Lan; Lu, Po-Liang; Cheng, Shu-Hsing; Lin, Chi-Ying; Wu, Ting-Shu; Yen, Muh-Yong; Wang, Lih-Shinn; Liu, Chang-Pan; et al.
Highlights: The incidence of adult invasive pneumococcal disease (IPD) dramatically decreased in the COVID-19 pandemic year 2020. The antimicrobial susceptibility rate was high for vancomycin and linezolid, followed by ceftaroline (non-meningitis). The MIC50 and MIC90 values of dalbavancin, telavancin, tedizolid, eravacycline, and omadacycline were generally low. Non-vaccine serotype 23A was the leading cause of adult IPD. The overall case fatality rate was 15.2% but was especially high for non-PCV-13 serotype 15B (21.4%). ABSTRACT: Objectives: The aim of this study was to investigate the trends in serotypes and in vitro antimicrobial susceptibility of Streptococcus pneumoniae causing adult invasive pneumococcal disease (IPD) to dalbavancin, telavancin, tedizolid, eravacycline, omadacycline and other comparator antibiotics from 2017–2020 following implementation of the 13-valent pneumococcal conjugate vaccine (PCV-13) and during the COVID-19 (coronavirus disease 2019) pandemic. Methods: During the study period, 237 S. pneumoniae isolates were collected from non-duplicate patients, covering 15.0% of IPD cases in Taiwan. Antimicrobial susceptibility testing was performed using a Sensititre® system. A latex agglutination method (ImmuLex™ Pneumotest Kit) was used to determine serotypes. Results: Susceptibility rates were high for vancomycin (100%), teicoplanin (100%) and linezolid (100%), followed by ceftaroline (non-meningitis) (98.3%), moxifloxacin (94.9%) and quinupristin/dalfopristin (89.9%). MIC50 and MIC90 values of dalbavancin, telavancin, tedizolid, eravacycline and omadacycline were generally low. Non-vaccine serotype 23A was the leading cause of IPD across the adult age range. Isolates of serotype 15B were slightly fewer than those of PCV-13 serotypes in patients aged ≥65 years. The overall case fatality rate was 15.2% (36/237) but was especially high for non-PCV-13 serotype 15B (21.4%; 3/14). Vaccine coverage was 44.7% for PCV-13 and 49.4% for the 23-valent pneumococcal polysaccharide vaccine (PPSV-23), but was 57% for both PCV-13 and PPSV-23. Conclusion: The incidence of IPD was stationary after PCV-13 introduction and only dramatically decreased in the COVID-19 pandemic in 2020. The MIC50 and MIC90 values of dalbavancin, telavancin, tedizolid, eravacycline, omadacycline were generally low for S. pneumoniae causing adult IPD.